Mitochondrial MPTP: A Novel Target of Ethnomedicine for Stroke Treatment by Apoptosis Inhibition - Li, Yangxin; Sun, Jiayi; Wu, Ruixia; Bai, Jinrong; Hou, Ya; Zeng, Yong; Zhang, Yi; Wang, Xiaobo; Wang, Zhang; Meng, Xianli (Frontiers in Pharmacology, 2020)
Mammalian mitochondrial permeability transition pore (MPTP), across the inner and outer membranes of mitochondria, is a nonspecific channel for signal transduction or material transfer between mitochondrial matrix and cytoplasm such as maintenance of calcium (Ca2+) homeostasis, regulation of oxidative stress signals, and protein translocation evoked by some of the stimuli. Continuous openness of MPTP has been proved to stimulate neuronal apoptosis in ischemic stroke. Meanwhile, inhibition of MPTP overopening-induced apoptosis have shown excellent efficacy in the treatment of clinical stroke and in basic preclinical studies. Among of which, the potential molecular mechanism of drug therapy for stroke, under the guidance of unique ethnic medicine theory, has also been gradually revealed by researchers. What’s striking is that the characteristics of multi-component or multi-target ethnic drugs, as well as improved neurobehavioral manifestations and numerous apoplexy sequelae or complications that cannot be solved by western medicine, also provide the possibility to treat stroke from the perspective of mitochondrial MPTP. The advantages mentioned above make it necessary for us to explore and clarify the new perspective of ethnic medicine in treating stroke and to clarify the specific molecular mechanism through advanced technology as much as possible. In this review, we attempted to uncover the relationship between abnormal MPTP opening and neuronal apoptosis in ischemic stroke. We further summarized the currently authorized drugs, ethnic medicine prescriptions, herbs and identified monomer compounds for inhibition of MPTP overopening-induced ischemic neuron apoptosis. Finally, we strive to provide a new perspective and enlightenment for ethnic medicine in the prevention and treatment of stroke by inhibition of MPTP overopening-induced neuronal apoptosis.